2014
DOI: 10.1158/0008-5472.can-13-2908
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 and Tim-3 Regulate the Expansion of Tumor Antigen–Specific CD8+ T Cells Induced by Melanoma Vaccines

Abstract: Although melanoma vaccines stimulate tumor antigen (TA)-specific CD8+ T cells, objective clinical responses are rarely observed. To investigate this discrepancy, we evaluated the character of vaccine-induced CD8+ T cells with regard to the inhibitory T cell co-receptors PD-1 and Tim-3 in metastatic melanoma patients who were administered tumor vaccines. The vaccines included incomplete Freund's adjuvant (IFA), CpG oligodeoxynucleotide (CpG) and the HLA-A2-restricted analog peptide NY-ESO-1 157-165V, either by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 26 publications
8
132
1
2
Order By: Relevance
“…62 Additionally, TIM-3 is highly expressed on effector immune cells such as T cells and NK cells, and serves as an exhaustion marker for T cells and NK cells. 45,46,53 Together, these results suggest that the manipulation of TIMs functions by mAbs is a promising and powerful strategy to initiate or amplify an existing immune response against tumors (Fig. 2).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…62 Additionally, TIM-3 is highly expressed on effector immune cells such as T cells and NK cells, and serves as an exhaustion marker for T cells and NK cells. 45,46,53 Together, these results suggest that the manipulation of TIMs functions by mAbs is a promising and powerful strategy to initiate or amplify an existing immune response against tumors (Fig. 2).…”
Section: Resultsmentioning
confidence: 84%
“…TIM-3 interacts with galectin-9 and causes exhaustion and apoptosis of antigenspecific CTLs, which correlates with impaired antitumor immune responses. 45,46 TIM-3 expression was also observed on Foxp3 C regulatory T cells; however, the function of TIM-3 in this population should be explored in future studies. 47 Several blocking mAbs have been generated to target mouse and human TIM-3 ( Table 2).…”
Section: -16mentioning
confidence: 96%
See 1 more Smart Citation
“…85 Vaccination results in upregulation of immune checkpoint receptors (e.g., PD1 receptor and T-cell membrane protein 3 (TIM3) that suppresses Th1 cell activation) and induction of Tcell anergy. 86 Studies are being conducted on immune checkpoint inhibitors combined with anti-angiogenic agents or DCbased vaccines in mRCC. Synergy between an anti-PD-L1 antibody and a vaccine against human papillomavirus was shown.…”
Section: Counteracting the Immunosuppressive Environmentmentioning
confidence: 99%
“…A team of U.S. researchers has found that combining a cocktail of antibodies targeting checkpoint proteins with peptide-based cancer vaccines induced a potent and tumor-specific T cell response to treat melanoma. 1 Researchers on the paper founded cancer immunology company CoStim Pharmaceuticals Inc. in 2011. The company is developing combinations of undisclosed checkpoint inhibitors.…”
mentioning
confidence: 99%